Sistem Informasi Promosi Pada Teknos Genius Jambi Berbasis Web - Indrianti, Inne; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2023)
Teknos Genius Jambi is an example of informal education that teaches elementary to high school students in Jambi City. Teknos Genius Jambi in promotion found problems, namely: limited dissemination of information and promotion, registration process that takes a long time, and errors in processing student payment contribution data both from calculations and data recording. The solution of the problems that occur by analyzing and designing promotional information systems using prototype development methods and unified model language system models using usecase diagrams, activity diagrams, and class diagrams. The results of the system development can display class data, student data, package data, teacher data, payment data, information data, and forum data in a structured manner and display the necessary reports